Prof. Dr. Katarina Čufar received the Jesenko Lifetime Achievement Award - Marko Petrič; Milan Šernek (Les)
In March 2021, Prof. Dr. Katarina Čufar received the Jesenko Lifetime Achievement Award, the most prestigious prize of the Biotechnical Faculty, University of Ljubljana. This is the third award for Katarina Čufar within just a few months, as at the end of 2020 she also received the Golden Plaque from the University of Ljubljana and the Zois Prize of the Republic of Slovenia for significant scientific achievements and exemplary teaching.